SURVEI STATUS GIZI DAN KETERAMPILAN MOTORIK PADA PESERTA DIDIK KELAS VII SMPN 3 MALANG - Syarif Hidayatullah; Usman Wahyudi; Dian Firmanto; Syarif Hidayatullah; Usman Wahyudi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This observation aims to determine the nutritional status and motor skills of classVII students at SMPN 3 Malang. The research approach uses an observationalapproach with descriptive research type. The research subjects were taking class VIIat SMPN 3 Malang with a total of 32 students. Data collection techniques used theBody Mass Index Test (BMI) and Kids Athletics instruments. From the researchresults, nutritional status in class VII is predominantly in the underweight categorywith a percentage of 42.5 percent with a total of 14 students. Furthermore, for the resultsof the kids athletics test in the turbo throwing number, boys have the highest scorein the adequate category with a percentage of 35.4percent, while girls in the poorcategory with a percentage of 47.2percent. In the frog jumping event, men had thehighest score in the fair and good category with a percentage of 35.4percent, whilewomen were in the poor category with a percentage of 38.1percent. In the Kanga runningnumber, the highest score for men was in the very good category with a percentageof 41.6percent, while for women the score was in the good category with a percentageof 38.2percent